Ketidakseimbangan Otot-otot Lumbopelvic Sebagai Faktor Kontributor Patellofemoral Pain Syndrome Pada Atlet Mahasiswa Basket Putri - Harijanto, Elbert Aldrin; Kurniarobbi, Jull (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Patellofemoral Pain Syndrome (PFPS) is a common cause of knee pain, often exacerbated by specific activities. Muscle imbalances, particularly in the thighs and hips, contribute to its development. Diagnosis relies on subjective and objective assessments, including specific tests. Case Illustration: We present a case of a 20-year-old female basketball player with PFPS symptoms, characterized by postural abnormalities, limited range of motion, and positive physical examination findings. Discussion: The patient's symptoms match PFPS. Postural assessment shows left posterior chain muscle stiffness and asymmetrical shoulder and hip alignment. Palpation reveals tenderness and tightness in the left quadriceps and hamstring. Limited active range of motion and limited ankle ROM support PFPS diagnosis. Basketball and gym exercises could worsen lower limb muscle overuse. Squat analysis indicates lumbopelvic instability with increased knee anteriorization. Greater hip adduction during lunges suggests weak gluteus medius. Asymmetrical lumbopelvic motion during single leg stance may indicate compensatory mechanisms. Navicular drop test shows more significant changes on the left side. Conclusion: Lumbopelvic imbalance contributes to PFPS in this patient, supported by symptoms and physical examination findings. Gender, thigh and hip muscle imbalances are contributing factors to PFPS.